Study on the Structured Processing of Unstructured Personalized Customer Requirement for Mass Customization - Qinglie Wu; Yu Guo (Dianxin kexue)
Mass customization is a new model of manufacturing and services. Customers' personalized service requirement in mass customization often have the unstructured characteristics, and obtaining and analyzing customers' real requirements accurately is the key to successful implementation of mass customization. The definition and determination methods of unstructured personalized customer requirements were proposed, and an analysis framework of unstructured personalized customer requirement in mass customization was built according to their characters. Then mapping rules and extended QFD were designed for the transformation from unstructured personalized customer requirement to structured product requirements. Finally the validity of the method was verified by an example and the method can be helpful to provide personalized cloud service.